Lingkungan Kerja terhadap Stres Kerja pada Pegawai - Marsya Sahsabilla; Resti Selfiah; Mira Veranita (IPM2KPE, 2022)
The purpose of this study was to determine the effect of the work environment on work stress on employees. This research method is descriptive quantitative. The total population at the Class I Penitentiary Bandung is 96 employees. The method of collecting data is through the distribution of questionnaires as a research instrument. The results showed that the work environment can affect employee work stress, based on the value of R2 (R Square) in this study was 0.883 or 88.3%, meaning that the influence of the independent variable was 88.3% while 11.7% was influenced by factors -other factors. In conclusion, at the Class I Penitentiary Bandung, the work environment (X) has a significant effect on work stress (Y) partially. Keywords: Work Environment, Work Stress